Estudio de factibilidad para la implementación de una fábrica de panela en la finca Charalapo del barrio Palmira, parroquia Quinara del cantón Loja - Torres Torres, Darwin Leodan (2016)
The Feasibility Study for the Implementation of a factory panela in Charalapo farm in the neighborhood Palmira, parish Quinara, Loja Canton, aimed to conduct a market study to determine the demand and supply of panela, determine the technical study to define the location, size and capacity, design the organizational and administrative structure for the implementation of the factory and determine the economic and financial feasibility of it. The methodology consisted of applying techniques such as direct observation, interviews and surveys through the instrument of the questionnaire applied to three bidders four sales intermediaries panela to consumer families and 383 people at random, the study variables were; market research, technical, organizational, economic, financial and environmental. In research methods, scientific method for obtaining necessary information from the theory of variables and analyze the results, analytical method for conducting the discussion, and inductive-deductive was used to draw the conclusions and recommendations. The results indicate that the unmet demand for panela in the city of Loja is 4'768.586,68 panelas of panelas purchased by consumers and intermediaries annually, for which the factory will start by covering with 576,000 panelas and projected to increase 2.23% market according to the annual population growth, projected in five years, according to the implemented machinery that is 288 tons / year. As for the technical study, the company will be located in the La Palmira of Quinara parish in the city of Loja, with an area of 1,200 square meters, with a total of seven people to run the company with a load capacity six tons per week. The investment cost for the implementation of the factory for production panela is $ 146,880.12, with an equity capital of $ 102,816.08 and $ 44,064.04 in funding. For every dollar invested you get $ 1.50 of profit. The unit cost of production of panela is $ 0.25, achieving sell at a price of $ 0.33 to intermediaries and Internal Rate of Return of 69.05% is allowed to determine that it is appropriate to invest in this draft. It is concluded that the demand for panela in Quinara parish presents qualitative and quantitative conditions potential to respond favorably to the production and marketing of the same as the prototype selected for processing if it meets the technical conditions of defined size in this study which the processing plant made in this feasibility study presents technical feasibility and economic feasibility for implementation. It is recommended that due to the large unmet demand increase the supply of panela and in turn achieve the increase of the market and the establishment of a partnership for marketing the product at the provincial level. In my personal opinion I believe that the feasibility study for implementation of a factory, is a way to manage and theoretically projecting market growth at the local level, this could help Ecuador's economy grow exponentially, as there will be more sources of work which is considered the most important variables in the administration are market research, technical, organizational, economic, financial and environmental.